A Five-Year strategic financial plan for Mabuhay Vinyl Corporation - Jhunard C. Bamuya, Rodelie Ashley P. Dionisio, Ma. Leonora Kate Elariog, Mariela Darlene Tiffanie A. Flores, Maria Kayla A. Nafarrete, Rica R. Ocampo, Airish Bhea Pacaanas 4 0 16; 5
Executive Summary: This paper presents the strategic financial planning analysis for Mabuhay Vinyl Corporation, focusing on the company's performance over recent years. It has made use of the entity's financial statements from years 2019 to 2024 and key financial ratios, the study aims to provide a comprehensive understanding of the company's profitability, liquidity, and overall financial stability. Through this analysis, the researchers identified both strengths and areas for improvement that could help the company optimize its financial performance and properly manage their liquidity. The researcher has made an observation that the company faces a significant challenge in the form of inefficient asset management. Specific issues include a longer collection period for receivables compared to payables, leading to cash flow mismatches. Additionally, the company incurs a 6% loss in opportunity costs due to idle funds that could otherwise be allocated to income-generating investments. Furthermore, Mabuhay Vinyl Corporation demonstrates slow revenue generation relative to the use of its assets and a high level of cost of goods sold (COGS), which reduces overall profitability. These inefficiencies underscore the need for strategic interventions to improve asset utilization and financial performance. One of the key recommendations is securing long-term contracts with textile companies like Indo-Phil Textile Mills to ensure consistent cash flow and stabilize demand. This strategy provides predictable revenue streams, reduces risks associated with late payments, and strengthens the company's financial foundation. Additionally, it enables better resource allocation, reduces idle funds, and supports reinvestment in growth areas, ultimately enhancing operational efficiency and long-term profitability.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2